TINGKAT KEPUASAN IBU TERHADAP PELAYANAN PERSALINAN OLEH TENAGA KESEHATAN DI WILAYAH PUSKESMAS MAYANG - Khofi Hadidi (Jurnal Kesehatan dr. Soebandi, 2014)
Current public views about the quality of health services are related to patient satisfaction which can affect public health and community welfare. Based on data obtained in the Mayang Community Health Center area, it shows that there is a lack of attention from officers, especially mothers who will give birth, so that the number of births delivered by dukun is higher than that of health workers. The purpose of this study was to determine the level of maternal satisfaction with delivery services by health workers to be improved. This research uses descriptive research. The sampling technique used was a total sampling technique using 52 mothers giving birth assisted by health workers in April 2008. The measuring instrument used in this study was a questionnaire. Based on the results of research conducted on the level of maternal satisfaction with childbirth services for health workers in the Mayang Health Center region shows that the level of satisfaction with the quality of delivery services by health workers in the Mayang Health Center area with the largest number said expectations and perceptions were satisfied at 31 mothers (57.4% ). And 23 mothers (42.6%) said they were very satisfied while there were no mothers who showed dissatisfaction and were very dissatisfied. The mother's satisfaction is obtained because the expectation value is in accordance with her perception.